When New Proletarians enter the scene: The brake (strike) of app delivery people in Brazil in July 2020 (Research, Society and Development, 2024)
The objective of this article is to analyze the underlying reasons that caused the first strike(break) of app delivery drivers that took place in Brazil in July 2020, in the midst of the COVID-19 pandemic, which gave rise to new proletarians on the Brazilian political scene, having as general frameworks the international struggles of workers against large delivery platforms, which emerged from the fourth industrial revolution and expanded from the crisis of capitalism in the years 2007-2008, in the so-called “uberization” wave. The research had two moments: a review of the bibliography on platform capitalism and the “fourth industrial revolution”, in addition to strike movements in other countries and, in the second moment, the application of a Google form with 286 participants about working conditions and participation in the 2020 break, using the “snowball” method, in addition to two interviews with two main leaders of the movement that broke out in Brazil that year. The conclusion we reach is that this is a highly precarious, super-exploitation movement of workers, with long working hours and low income that objectively clashes with the large companies of platform capitalism, moving from the “class in itself” stage to “class for itself”, in addition to having a completely horizontalist character, bypassing the old Brazilian union structures and having social networks as its main support point and its leaders. But this is a movement in transition to social security and labor regulations.